Neck Circumference as A Screening Tool to Predict Obesity: A Cross Sectional Study in Coastal Karnataka, India - Shreedhar, Shyamsundar; Naik, Prashant M; Geeta; Havale, Naveenkumar; Manjula MN (National Journal of Community Medicine, 2022)
Background: Obesity is a disease of public health importance impacting most body systems. It leads to a range of NCD’s. BMI is commonly used to classify overweight and obesity in adults. Others measurements such as WC and WHR are considered as acceptable measures of obesity. However in community settings these can be a time consuming method. Instead Neck circumference (NC) can be used to screen for obesity. Methodology: A cross sectional study conducted among 310 study participants in rural field practice area of Government medical college, Karwar. Socio demographic characteristics were collected using pre designed semi structured questionnaire and anthropometric measurements as per standard guidelines. Data analyzed using Epi-info 7.2 version. Statistical tests like Pearson’s correlation coefficient were used to assess correlation. NC cut off values were obtained from ROC. Results: In our study, the correlation of NC with BMI was highly correlated among both males(r=0.529), and females (r=0.565). Kappa statistics depicted moderate agreement with BMI [males (κ = 0.512) ; females (κ = 0.496) and NC in the study population. The cut-off values obtained for neck circumference using ROC curve for males (35.5cm) and females (31.5cm) were statically significant associated in comparison to BMI to determine obesity in both males (χ2 = 58.57, and females (χ2 = 21.54). Conclusion: This study concluded that men with NC ≥ 35.5 cms and females with NC ≥ 31.5 cms are to be considered obese. The sensitivity of this screening test for these cut-off’s was 79.83% and 82.4% in males and females respectively.